IMPLEMENTASI METODE ANAK HEBAT (AHE) TERHADAP KEMAMPUAN MEMBACA ANAK USIA 5-6 TAHUN DI LEMBAGA LES BACA UNIT 3625 CUPANG GEMPOL CIREBON - ahmad rifai; Arifah Tul Maula; vina Uctuvia (MASILE, 2025)
This study discusses the implementation of the Anak Hebat (AHE) method on the reading ability of children aged 5–6 years at the Reading Course Unit 3625 Cupang, Gempol, Cirebon. Some early childhood learners still experience difficulties in recognizing letters and understanding words in reading activities. The objectives of this study are to describe the implementation of the Anak Hebat (AHE) method in improving the reading skills of children aged 5–6 years, to describe the children's responses to its application, and to identify the supporting and inhibiting factors in its implementation.